Recent progress, challenges and outlook for multidisciplinary structural optimization of aircraft and aerial vehicles. (1st November 2022) - Corrado, G.; Ntourmas, G.; Sferza, M.; Traiforos, N.; Arteiro, A.; Brown, L.; Chronopoulos, D.; Daoud, F.; Glock, F.; Ninic, J.; Ozcan, E.; Reinoso, J.; et al.
Abstract: Designing an airframe is a complex process as it requires knowledge from multiple disciplines such as aerodynamics, structural mechanics, manufacturing, flight dynamics, which individually lead to very different optimal designs. Furthermore, the growing use of Carbon Fibre Reinforced Plastics (CFRP), while allowing for more design freedom, has at the same time increased the complexity of the structural designers job. This has sparked the development of Multidisciplinary Design Optimization (MDO), a framework aimed at integrating intelligence from multiple disciplines in one optimal design. Initially employed as a tool to coordinate the work of several design teams over months, MDO is now becoming an integrated software procedure which has evolved over the decades and has become a prominent tool in modern design of aerostructures. A modern challenge in airframe design is the early use of MDO, motivated by a pressing industrial need for an increased level of detail at the beginning of the design process, to minimize late setbacks in product development. Originally employed only during preliminary design, MDO has recently being pushed into early evaluation of conceptual designs with the outlook of becoming established in the conceptual stage. Using MDO during conceptual design is a promising way to address the paradox of design. By improving each concept, evaluating whether it is capable of meeting the design requirements and computing the sensitivities of various performance measures with respect to a design change, MDO enables designers to gain valuable knowledge in a design phase, in which most of the design freedom is still available. We hereby exhibit the contemporary trends of MDO with specific focus on composite aircraft and aerial vehicles. We present the recent developments and current state-of-the-art, describing the contemporary challenges and requirements for innovation that are in the development process by academic and industrial researchers, as well as the challenges designers face in further improving the MDO workflow. Within the European OptiMACS project, we devised a novel holistic MDO approach to integrate a number of solutions to challenges identified as industrial technological gaps. These include two-stage optimization for layers of composites, addressing the presence of process-induced distortions and consideration of advanced failure criteria, including refined local models in early design stages, and seamlessly integrating software tools in the design process. The proposed methods are integrated and tested for structural case studies and the obtained results show the potential benefits of their integration into MDO tools.